1997
DOI: 10.1111/j.1528-1157.1997.tb01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Long‐Term Lamotrigine in Epilepsy

Abstract: Summary:Purpose: To examine the safety of lamotrigine (LTG) used in general practice to treat epilepsy.Methods: Information was collected on 11,316 patients who were included in a noninterventional observational cohort study conducted by means of Prescription-Event Monitoring (PEM). A follow-up study provided information on the first 3,994 patients who had taken LTG for 3 6 months. Incidence density (ID) measurements were used to rank the frequency of the reported events.Results: Rash was the most frequently r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
7

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(89 citation statements)
references
References 9 publications
1
81
0
7
Order By: Relevance
“…Headache (37%), nausea (22%), abnormal coordination (12%), and skin rash (10%) were not statistically significant (35) ( Table 3). Available evidence suggests that LTG is well tolerated at higher maintenance doses (up to 700 mg/day) (36) and during long-term therapy (37).…”
Section: Adverse Experiencesmentioning
confidence: 99%
“…Headache (37%), nausea (22%), abnormal coordination (12%), and skin rash (10%) were not statistically significant (35) ( Table 3). Available evidence suggests that LTG is well tolerated at higher maintenance doses (up to 700 mg/day) (36) and during long-term therapy (37).…”
Section: Adverse Experiencesmentioning
confidence: 99%
“…The reduction observed in vitality caused by formulation B, although not significant, may be related to the increase in mean plasma concentration of LTG which can promote the occurrence of side effects (nausea, headache, depression, irritability and skin rash) (Mackay et al, 1997). Formulation C of LTG showed improvement only on the sociability domain of the QOLIE-31, reducing the final score of quality of life, but the alterations were not considered statistically significant (Table III).…”
Section: Resultsmentioning
confidence: 93%
“…1,18,19 Rare studies have reported side-effects after chronic use of LTG (ex, 6 months). 20 The study of Mackay et al 21 evaluated adverse-effects six months after LTG introMoreira B, Thomé-Souza S, Valente K duction. Rash and Steven-Johnsons syndrome were earlier manifestations, observed during introduction.…”
Section: Discussionmentioning
confidence: 99%